Secondary battery and electric device

By using the first graphite and the first silicon-carbon composite with a flatness of ≥2 in the negative electrode sheet of the secondary battery, the problem of reduced circulation performance caused by volume expansion during charging of the silicon-based material is solved, and a more stable Pole-piece structure and longer battery life.

CN119447173APending Publication Date: 2025-02-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202310952247.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The silicon-based material expands in large volume during charging of the secondary battery, resulting in a reduced cycling performance of the battery.

Method used

The first graphite with a flatness of ≥2 and the first silicon-carbon composite are used in combination. The volume of the silicon-carbon composite expands during the buffer charging process to improve the stability of the electrode sheet structure.

Benefits of technology

It improves the cycling performance of the battery, improves the stability of the pole chip structure, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447173A_ABST
    Figure CN119447173A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electric device. The secondary battery comprises a negative pole piece, wherein the negative pole piece comprises a negative current collector and a first active layer positioned on at least one surface of the negative current collector; the first active layer comprises first graphite and a first silicon-carbon compound, the flatness of the first graphite is larger than or equal to 2, and the first silicon-carbon compound comprises a porous carbon base material and a silicon-based material located in pores of the porous carbon base material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] Silicon-based materials have a high gram capacity, and applying them to the negative electrode of secondary batteries can make the battery have a higher energy density. However, after charging, the volume of silicon-based materials expands greatly, which reduces the cycle performance of the battery. Summary of the invention

[0004] In order to achieve the above objectives, the present application provides a secondary battery with good cycle performance.

[0005] The present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode active layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active layer comprises a first active layer; the first active layer comprises a first graphite and a first silicon-carbon composite, the flatness of the first graphite is ≥2, and the first silicon-carbon composite comprises a porous carbon substrate and a silicon-based material located in the pores of the porous carbon substrate.

[0006] In the above-mentioned secondary battery, the first graphite with a flatness of ≥2 and the first silicon-carbon composite are used together to buffer the volume expansion of the silicon-carbon composite during charging, improve the stability of the pole piece structure, and thus improve the cycle performance of the battery.

[0007] In some embodiments, the flatness of the first graphite is 2.5 to 20. The flatness of the first graphite in this range can further improve the stability of the pole piece structure. Optionally, the flatness of the first graphite is 4 to 16.

[0008] In some embodiments, the first graphite includes primary particles. The primary particles have a relatively suitable flatness, which is more conducive to improving the pressure resistance of the first active layer. Optionally, the primary particles account for ≥90% of the first graphite.

[0009] In some embodiments, the volume average particle size Dv50 of the first graphite is 12 μm to 18 μm. The volume average particle size Dv50 of the first graphite within this range is conducive to obtaining a larger compaction density. Optionally, the volume average particle size Dv50 of the first graphite is 14 μm to 16 μm.

[0010] In some embodiments, the specific surface area of ​​the first graphite is 0.6 m 2 / g~1.4m 2 / g. The specific surface area of ​​the first graphite within this range can provide a suitable porosity, can further improve the energy density of the secondary battery, and can make the electrolyte fully contact with the first active layer, while taking into account good dynamic performance. Optionally, the specific surface area of ​​the first graphite is 0.8m 2 / g~1.2m 2 / g.

[0011] In some embodiments, the first graphite includes artificial graphite and / or natural graphite. Artificial graphite has good cycle performance, which is beneficial to improving the cycle performance of the secondary battery. Natural graphite has good compressive resistance, which is beneficial to improving the pressure resistance of the first active layer. Optionally, the first graphite includes natural graphite, and the mass percentage of the natural graphite in the first graphite is ≤20%.

[0012] In some embodiments, the volume average particle size Dv50 of the first silicon-carbon composite is 5 μm to 13 μm. If the volume average particle size Dv50 of the first silicon-carbon composite is too large, it may restrict the charging performance of the secondary battery. If the volume average particle size Dv50 of the first silicon-carbon composite is too small, the brittleness of the first active layer may be too high, causing cracks in the negative electrode sheet during charging, affecting the performance of the battery. Optionally, the volume average particle size Dv50 of the first silicon-carbon composite is 7 μm to 11 μm.

[0013] In some embodiments, the specific surface area of ​​the first silicon-carbon composite is 1 m 2 / g~8m 2 / g. If the specific surface area of ​​the first silicon-carbon composite is too large, poor cycle performance and storage performance may occur. If the specific surface area of ​​the first silicon-carbon composite is too small, the porosity of the first silicon-carbon composite may be small, thereby causing poor dynamic performance of the battery. Optionally, the volume average particle size Dv50 of the first silicon-carbon composite is 1m 2 / g~5m 2 / g.

[0014] In some embodiments, the mass percentage of the first silicon-carbon composite in the first active layer is 5% to 50%. In the first active layer, if the mass percentage of the first silicon-carbon composite is too small, the effect of improving the energy density of the corresponding battery is not obvious. If the mass percentage of the first silicon-carbon composite is too large, the effect of improving the compaction density is not obvious.

[0015] In some embodiments, the mass percentage of the porous carbon substrate in the first silicon-carbon composite is ≥40%. In the first silicon-carbon composite, if the mass percentage of the porous carbon substrate is too small, the conductivity of the first silicon-carbon composite may be poor, resulting in poor battery performance. If the mass percentage of the porous carbon substrate is too large, the mass percentage of the corresponding silicon-based material may be too low, and the effect of improving the battery energy density is not obvious. Optionally, the mass percentage of the porous carbon substrate in the first silicon-carbon composite is 40% to 60%.

[0016] In some embodiments, the porosity of the porous carbon substrate is 30% to 60%. A porous carbon substrate with too small a porosity may result in poor kinetic performance of the battery. A porous carbon substrate with too large a porosity may result in poor cycle performance and storage performance of the battery.

[0017] In some embodiments, the mass percentage of the silicon-based material in the first silicon-carbon composite is ≤ 60%. In the first silicon-carbon composite, if the mass percentage of the silicon-based material is too large, the pressure resistance of the first active layer may be poor. At the same time, if the mass percentage of the silicon-based material is too large, the expansion rate of the first silicon-carbon composite material may increase, thereby causing poor structural stability of the negative electrode plate during charging. Optionally, the mass percentage of the silicon-based material in the first silicon-carbon composite is 40% to 60%.

[0018] In some embodiments, the silicon-based material includes nano-silicon, and optionally, the grain size of the nano-silicon is ≤6 nm. In the first silicon-carbon composite, the grain size of the nano-silicon is relatively small, so that the first silicon-carbon composite has better cycle performance.

[0019] In some embodiments, the negative electrode active layer further includes a second active layer; the second active layer is located on a surface of the first active layer away from the negative electrode current collector, and the second active layer includes a second graphite. The overall compaction density of the negative electrode sheet can be further improved by providing the second active layer.

[0020] In some embodiments, the surface of the second graphite is coated with a carbon coating layer. The provision of the carbon coating layer can improve the overall conductivity of the second graphite and improve the fast charging performance of the secondary battery. Optionally, the thickness of the carbon coating layer is 10nm to 300nm, and further optionally 20nm to 100nm.

[0021] In some embodiments, the second graphite includes secondary particles. The introduction of secondary particles can further improve the charging performance of the secondary battery. Optionally, the amount of the secondary particles in the second graphite accounts for ≥50%, and can be 50% to 90%.

[0022] In some embodiments, the volume average particle size Dv50 of the second graphite is smaller than the volume average particle size Dv50 of the first graphite. The volume average particle size Dv50 of the second graphite is smaller, which can reduce the transmission path of lithium ions, which is beneficial to improve the dynamic performance of the negative electrode plate, thereby improving the fast charging performance of the battery. Optionally, the volume average particle size Dv50 of the second graphite is 9μm to 15μm, and further optionally 11μm to 13μm.

[0023] In some embodiments, the specific surface area of ​​the second graphite is greater than the specific surface area of ​​the first graphite. This is beneficial to improve the cycle performance of the battery. Optionally, the specific surface area of ​​the second graphite is 0.8 m 2 / g~1.6m 2 / g, further optionally 1m 2 / g~1.4m 2 / g.

[0024] In some embodiments, the second active layer further comprises a second silicon-carbon composite. The second active layer further comprises a second silicon-carbon composite, which can further improve the energy density of the secondary battery. Optionally, the material of the second silicon-carbon composite includes the material of the first silicon-carbon composite.

[0025] In some embodiments, the mass percentage of the second silicon-carbon composite in the second active layer is 5% to 50%. In the second active layer, if the mass percentage of the second silicon-carbon composite is too small, the effect of improving the energy density of the corresponding battery is not obvious. If the mass percentage of the second silicon-carbon composite is too large, the effect of improving the compaction density is not obvious.

[0026] The present application also provides an electrical device, comprising the above-mentioned secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0028] Figure 1 This is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0029] Figure 2 for Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0030] Figure 3 FIG. 1 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.

[0031] Description of reference numerals:

[0032] 1. Secondary battery; 11. Casing; 12. Electrode assembly; 13. Cover plate; 2. Electrical device.

[0033] In order to better describe and illustrate the embodiments and / or examples of the inventions disclosed herein, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered to limit the scope of the disclosed inventions, the embodiments and / or examples currently described, and any of the best modes of these inventions currently understood. DETAILED DESCRIPTION

[0034] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0036] The "range" disclosed in the present application can be defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and any end value can be included or excluded independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0037] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0039] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0040] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0041] In this application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A includes not only a1, a2 and a3, but also other members".

[0042] In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0043] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0044] An embodiment of the present application provides a secondary battery, including a negative electrode plate, the negative electrode plate including a negative electrode current collector and a negative electrode active layer located on at least one surface of the negative electrode current collector, the negative electrode active layer including a first active layer; the first active layer includes a first graphite and a first silicon-carbon composite, the flatness of the first graphite is ≥2, and the first silicon-carbon composite includes a porous carbon substrate and a silicon-based material located in the pores of the porous carbon substrate. In the secondary battery of this embodiment, the first graphite with a flatness of ≥2 and the first silicon-carbon composite are used together, which can buffer the volume expansion of the silicon-carbon composite during charging, improve the stability of the plate structure, and thus improve the cycle performance of the battery.

[0045] At the same time, using the first graphite with a flatness ≥ 2 and the first silicon-carbon composite together can alleviate the brittle change of the silicon-carbon composite during the charging process and further improve the stability of the pole piece structure.

[0046] In the present application, flatness is expressed as the ratio of the major diameter to the thickness of the particle, wherein the smallest dimension is the thickness, the largest dimension is the major diameter, and the dimension in the middle is the minor diameter. That is, the flatness of the first graphite represents the ratio of the major diameter to the thickness of the first graphite particle.

[0047] In the present application, the flatness can be tested in the following way: first, the electrode is cut into a size of 6mm×6mm and attached to an ion polisher, cut at a voltage of 7.5kV for 30 minutes, and tested and observed using a Sigma300 scanning electron microscope & energy spectrometer in accordance with the JY / T010-1996 test standard. At least 20 graphite particles are selected, the ratio of the major diameter to the thickness of each graphite particle is calculated, and the average value is taken to obtain the flatness of the corresponding graphite.

[0048] Optionally, the first graphite comprises flake graphite. Further optionally, the first graphite comprises flaky graphite.

[0049] In some embodiments, the flatness of the first graphite is 2.5 to 20. The flatness of the first graphite in this range can further improve the stability of the pole piece structure. Optionally, the flatness of the first graphite can be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc. Optionally, the flatness of the first graphite is 4 to 16. For example, the flatness of the first graphite can range from 2 to 8, 2 to 4, 4 to 8, etc.

[0050] In some embodiments, the surface of the first graphite does not contain a carbon coating layer. Carbon coating the first graphite can improve the overall conductivity of the first graphite, and thus may improve the fast charging performance of the battery. However, the introduction of the carbon coating layer may increase the overall hardness of the first graphite, restricting the improvement of the compaction density of the first active layer.

[0051] In some embodiments, the first graphite includes primary particles. The primary particles have a relatively suitable flatness, which is more conducive to improving the pressure resistance of the first active layer. Optionally, the number of primary particles in the first graphite accounts for ≥90%. For example, the number of primary particles in the first graphite accounts for 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc. Further optionally, the number of primary particles in the first graphite accounts for 95% to 100%.

[0052] In some embodiments, the first graphite also includes secondary particles, and the number of secondary particles in the first graphite accounts for ≤10%. When the first graphite also includes secondary particles, the fast charging performance of the secondary battery is improved to a certain extent. However, compared with the primary particles, the secondary particles have a higher sphericity. When the number of secondary particles in the first graphite accounts for too large a proportion, the improvement in the voltage resistance of the first active layer is limited. Further optionally, the number of secondary particles in the first graphite accounts for ≤9%, ≤8%, ≤7%, ≤6%, ≤5%, ≤4%, ≤3%, ≤2% or ≤1%, etc.

[0053] As some examples of the selection of the first graphite particle size, the volume average particle size Dv50 of the first graphite is 12 μm to 18 μm. The volume average particle size Dv50 of the first graphite is advantageous for obtaining a larger compaction density within this range. Optionally, the Dv50 of the first graphite is 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm, etc. Further optionally, the Dv50 of the first graphite is 14 μm to 16 μm.

[0054] It is understood that in this application, Dv50 refers to the particle size corresponding to when the cumulative particle size distribution number of particles reaches 50% in the volume cumulative distribution curve. Its physical meaning is that particles with a particle size smaller than (or larger than) it account for 50%. As an example, Dv50 can be obtained by referring to the GB / T 19077-2016 test method and using the particle size distribution curve obtained by the laser diffraction particle size distribution measuring instrument Mastersizer3000.

[0055] As some examples of the selection of the specific surface area of ​​the first graphite, the specific surface area of ​​the first graphite is 0.6 m 2 / g~1.4m 2 / g. The specific surface area of ​​the first graphite within this range can provide a suitable porosity, which can further improve the energy density of the secondary battery, and at the same time allow the electrolyte to fully contact the first active layer, taking into account good dynamic performance. Optionally, the specific surface area of ​​the first graphite is 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g or 1.4m 2 / g, etc. Further optionally, the specific surface area of ​​the first graphite is 0.8m 2 / g~1.2m 2 / g.

[0056] In the present application, the test method of specific surface area can refer to GB / T 19587-2004 gas adsorption BET method for determining the specific surface area of ​​solid substances, and the nitrogen adsorption specific surface area analysis test method is used for testing, and the specific surface area analysis test is calculated using the BET (BrunauerEmmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed using the Tni StarlI 3020 specific surface and pore analyzer of Micromeritics Corporation of the United States.

[0057] In some embodiments, the first graphite includes artificial graphite and / or natural graphite. Artificial graphite has good cycle performance, which is beneficial to improving the cycle performance of the secondary battery. Natural graphite has good compressive performance, which is beneficial to improving the compressive performance of the first active layer.

[0058] Optionally, the first graphite includes natural graphite, and the mass percentage of natural graphite in the first graphite is ≤20%. When the amount of natural graphite is large, the improvement of battery cycle performance may be limited. Further optionally, the mass percentage of natural graphite in the first graphite is ≤18%, ≤15%, ≤12%, ≤10%, ≤8%, ≤5%, ≤2% or ≤1%, etc.

[0059] As some selected examples of the particle size of the first silicon-carbon composite, the volume average particle size Dv50 of the first silicon-carbon composite is 5μm to 13μm. If the volume average particle size Dv50 of the first silicon-carbon composite is too large, it may restrict the charging performance of the secondary battery. If the volume average particle size Dv50 of the first silicon-carbon composite is too small, the brittleness of the first active layer may be too high, causing cracks in the negative electrode sheet during charging, affecting the performance of the battery. Optionally, the volume average particle size Dv50 of the first silicon-carbon composite is 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or 13μm, etc. Further optionally, the volume average particle size Dv50 of the first silicon-carbon composite is 7μm to 11μm.

[0060] In some embodiments, the specific surface area of ​​the first silicon-carbon composite is 1 m 2 / g~8m 2 / g. If the specific surface area of ​​the first silicon-carbon composite is too large, the cycle performance and storage performance may be poor. If the specific surface area of ​​the first silicon-carbon composite is too small, the porosity of the first silicon-carbon composite may be small, thereby causing poor dynamic performance of the battery. Optionally, the specific surface area of ​​the first silicon-carbon composite is 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g or 8m 2 / g, etc. Further optionally, the specific surface area of ​​the first silicon-carbon composite is 1m 2 / g~5m 2 / g.

[0061] In some embodiments, the mass percentage of the first silicon-carbon composite in the first active layer is 5% to 50%. In the first active layer, if the mass percentage of the first silicon-carbon composite is too small, the effect of improving the energy density of the corresponding battery is not obvious. If the mass percentage of the first silicon-carbon composite is too large, the effect of improving the compaction density is not obvious. Optionally, the mass percentage of the first silicon-carbon composite in the first active layer is 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 35%, 40%, 45% or 50%, etc.

[0062] In some embodiments, the mass percentage of the porous carbon substrate in the first silicon-carbon composite is ≥40%. In the first silicon-carbon composite, if the mass percentage of the porous carbon substrate is too small, the conductivity of the first silicon-carbon composite may be poor, resulting in poor performance of the battery. If the mass percentage of the porous carbon substrate is too large, the mass percentage of the corresponding silicon-based material may be too low, and the effect of improving the energy density of the battery is not obvious. Optionally, the mass percentage of the porous carbon substrate in the first silicon-carbon composite is 40% to 60%. Further optionally, the mass percentage of the porous carbon substrate in the first silicon-carbon composite is 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58% or 60%, etc.

[0063] In some embodiments, the porosity of the porous carbon substrate is 30% to 60%. If the porosity of the porous carbon substrate is too small, the kinetic performance of the battery may be poor. If the porosity of the porous carbon substrate is too large, the cycle performance and storage performance of the battery may be poor. Optionally, the porosity of the porous material is 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58% or 60%, etc.

[0064] In some embodiments, the mass percentage of silicon-based materials in the first silicon-carbon composite is ≤60%. In the first silicon-carbon composite, too large a mass percentage of silicon-based materials may cause the first active layer to have poor pressure resistance. At the same time, too large a mass percentage of silicon-based materials may also increase the expansion rate of the first silicon-carbon composite material, thereby causing poor structural stability of the negative electrode during charging. Optionally, the mass percentage of silicon-based materials in the first silicon-carbon composite is 40% to 60%. Further optionally, the mass percentage of silicon-based materials in the first silicon-carbon composite is 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58% or 60%, etc.

[0065] In some embodiments, the silicon-based material includes nano-silicon, and optionally, the grain size of the nano-silicon is ≤6nm. In the first silicon-carbon composite, the grain size of the nano-silicon is relatively small, so that the first silicon-carbon composite has better performance. Optionally, the grain size of the nano-silicon is ≤5nm, ≤4nm, ≤3nm, ≤2nm or ≤1nm, etc.

[0066] It can be understood that the content of silicon and carbon in the silicon-carbon composite can be tested by the following method: first, cut the electrode into a size of 6mm×6mm, and stick it on an ion polishing machine, cut it at a voltage of 7.5kV for 30 minutes, and according to the JY / T010-1996 test standard, use a Sigma300 scanning electron microscope & energy spectrometer to scan the regional elements, and you can get the proportion of silicon and carbon in the silicon-carbon composite.

[0067] In some embodiments, the negative electrode active layer further includes a second active layer; the second active layer is located on a surface of the first active layer away from the negative electrode current collector, and the second active layer includes a second graphite. The second active layer can further improve the overall compaction density of the negative electrode sheet.

[0068] Optionally, the surface of the second graphite is coated with a carbon coating. At this time, the overall conductivity of the second graphite can be improved by setting the carbon coating, and the fast charging performance of the secondary battery can be improved. Optionally, the thickness of the carbon coating is 10nm to 300nm. For example, the thickness of the carbon coating is 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 150nm, 200nm, 250nm or 300nm, etc. Further optionally, it is 20nm to 100nm.

[0069] In some embodiments, the second graphite includes secondary particles. The introduction of secondary particles can further improve the charging performance of the secondary battery. Optionally, the number of secondary particles in the second graphite accounts for ≥50%. Further optionally, the number of secondary particles in the second graphite accounts for ≥50%, ≥60%, ≥70%, ≥80% or ≥90%, etc. Further optionally, the second graphite is secondary particles.

[0070] In some embodiments, the volume average particle size Dv50 of the second graphite is smaller than the volume average particle size Dv50 of the first graphite. The volume average particle size Dv50 of the second graphite is smaller, which can reduce the transmission path of lithium ions, which is beneficial to improve the dynamic performance of the negative electrode plate, and thus improve the fast charging performance of the battery. Optionally, the volume average particle size Dv50 of the second graphite is 9μm to 15μm. For example, the volume average particle size Dv50 of the second graphite is 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm, etc. Further optionally, the volume average particle size Dv50 of the second graphite is 11μm to 13μm.

[0071] In some embodiments, the specific surface area of ​​the second graphite is greater than the specific surface area of ​​the first graphite. This is beneficial to improve the cycle performance of the battery. Optionally, the specific surface area of ​​the second graphite is 0.8 m 2 / g~1.6m 2 / g. For example, the specific surface area of ​​the second graphite is 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g or 1.6m 2 / g, etc. Further optionally, the specific surface area of ​​the second graphite is 1m 2 / g~1.4m 2 / g.

[0072] In some embodiments, the second graphite includes artificial graphite, which can further improve the cycle performance of the battery.

[0073] In some embodiments, the second active layer further comprises a second silicon-carbon composite. The second active layer further comprises a second silicon-carbon composite, which can further improve the energy density of the secondary battery.

[0074] Optionally, the material of the second silicon-carbon composite includes the material of the first silicon-carbon composite. For example, the second silicon-carbon composite includes a porous carbon substrate and a silicon-based material located in the pores of the porous carbon substrate. The volume average particle size Dv50 of the second silicon-carbon composite is 5 μm to 13 μm, and optionally 7 μm to 11 μm. The specific surface area of ​​the second silicon-carbon composite is 1 m 2 / g~8m 2 / g, optionally 1m 2 / g~5m 2 / g. The mass percentage of the porous carbon substrate in the second silicon-carbon composite is ≥40%, optionally 40% to 60%. The porosity of the porous carbon substrate is 30% to 60%. The mass percentage of the silicon-based material in the second silicon-carbon composite is ≤60%, optionally 40% to 60%. The silicon-based material includes nano-silicon, and the grain size of the nano-silicon is ≤6nm. Optionally, the corresponding features of the second silicon-carbon composite can be correspondingly selected from the features of the above-mentioned first silicon-carbon composite.

[0075] It is understood that the second silicon-carbon composite is the same as the first silicon-carbon composite.

[0076] In some embodiments, the mass percentage of the second silicon-carbon composite in the second active layer is 5% to 50%. In the second active layer, if the mass percentage of the second silicon-carbon composite is too small, the effect of improving the energy density of the corresponding battery is not obvious. If the mass percentage of the second silicon-carbon composite is too large, the effect of improving the compaction density is not obvious. Optionally, the mass percentage of the second silicon-carbon composite in the second active layer is 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 35%, 40%, 45% or 50%, etc.

[0077] In some embodiments, the silicon-carbon composite can be prepared by depositing a silicon-based material in the pores of a porous carbon substrate. Alternatively, the silicon-based material can be deposited in the pores of a porous carbon substrate by vapor deposition to obtain the silicon-carbon composite.

[0078] Optionally, the method for preparing the silicon-carbon composite comprises:

[0079] S101: placing the porous carbon substrate in a vapor deposition furnace, keeping the furnace body rotating, purging with an inert gas and preheating to 200° C. to 300° C. Optionally, the porosity of the porous carbon substrate is 30% to 60%. Optionally, the inert gas includes at least one of nitrogen and argon. Optionally, the porous carbon substrate includes at least one of activated carbon, biomass carbon and resin carbon.

[0080] S102: A mixed gas of silicon source gas and inert gas is introduced in a certain proportion to control the pressure in the furnace to be in a slightly positive pressure range. Optionally, the volume fraction of the silicon source gas in the mixed gas is 5% to 30%. Optionally, the pressure in the furnace is controlled to be 200Pa to 600Pa higher than the standard atmospheric pressure. Optionally, the silicon source gas includes at least one of monosilane and disilane.

[0081] S103: Continue to raise the temperature to 500°C to 700°C and deposit for 2h to 12h.

[0082] S104: Turn off the silicon source gas, adjust the temperature to 600°C to 800°C, introduce the carbon source gas, and deposit for 2h to 12h. Screen the silicon-carbon composite after it is taken out of the furnace. Optionally, the volume fraction of the carbon source gas in the mixed gas is 5% to 20%. Optionally, the carbon source gas includes at least one of methane, ethylene and acetylene.

[0083] Another embodiment of the present application provides an electric device, which includes the secondary battery mentioned above.

[0084] The secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0085] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0086] Positive electrode

[0087] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0088] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0089] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0090] In some of the embodiments, the positive electrode active material may be a positive electrode active material for a battery known in the art. As a non-limiting example, the positive electrode active material may include one or more of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Non-limiting examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.85 Co 0.15 Al 0.05 O2.

[0091] In some of these embodiments, the positive electrode active material layer may also optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0092] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0093] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt% to 80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000-25000mPa·s. When applying the positive electrode slurry, the coating unit area density based on dry weight (excluding solvent) can be 15-35 mg / cm 2 The compaction density of the positive electrode sheet can be 3.0-3.6 g / cm 3 , can be selected as 3.3~3.5g / cm 3 .

[0094] Negative electrode

[0095] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0096] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0097] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0098] In some of the embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0099] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0100] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0101] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0102] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt% to 60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000-10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75-220g / m 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~1.8g / cm 3 .

[0103] Electrolytes

[0104] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0105] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0106] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0107] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, ), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethylene carbonate One or more of fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0108] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0109] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.

[0110] Isolation film

[0111] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0112] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0113] In some embodiments, the isolation film has a thickness of 6 to 40 μm, and may be 12 to 20 μm.

[0114] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0115] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0116] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0117] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.

[0118] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.

[0119] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. For example, Figure 1 The battery cell 1 is a square structure as an example.

[0120] In some of these embodiments, reference Figure 2 , the outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 1 can be one or more, and those skilled in the art can select according to actual needs.

[0121] The secondary battery may be a battery module or a battery pack.

[0122] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.

[0123] In the battery module, the plurality of battery cells may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells may be fixed by fasteners.

[0124] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of battery cells are accommodated in the accommodation space.

[0125] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0126] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.

[0127] In addition, the present application also provides an electrical device, which includes a secondary battery provided by the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.

[0128] As an electrical device, a secondary battery can be selected according to its usage requirements.

[0129] Figure 3 The power consumption device 2 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0130] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0131] Example

[0132] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0133] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0134] The preparation method of the secondary battery is as follows:

[0135] (1) Preparation of silicon-carbon composites

[0136] S101: Place a biomass porous carbon substrate with a porosity of 50% in a vapor deposition furnace, keep the furnace body rotating, purge it with nitrogen and pre-heat it to 200°C.

[0137] S102: A mixed gas of silane gas and nitrogen is introduced at a ratio of 1:4, and the pressure in the furnace is controlled to be 300Pa higher than the standard atmospheric pressure.

[0138] S103: Continue heating to 500°C and deposit for 8 hours.

[0139] S104: Turn off the silane gas, adjust the temperature to 620°C, introduce acetylene gas at a flow rate of 10%, and deposit for 2 hours. Screen out of the furnace to obtain a silicon-carbon composite, wherein the silicon-carbon composite includes a porous carbon substrate and a silicon-based material located in the pores of the porous carbon substrate.

[0140] (2) Preparation of negative electrode sheet

[0141] The first graphite, the first silicon-carbon composite, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene-butadiene rubber are mixed, deionized water is added, and the mixture is stirred in vacuum to obtain a first slurry with a solid content of 49%.

[0142] The second graphite, the second silicon-carbon composite, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene-butadiene rubber were mixed, deionized water was added, and the mixture was stirred in vacuum to obtain a second slurry with a solid content of 49%.

[0143] ① When the negative electrode sheet only includes the first active layer, the first slurry is coated on the current collector copper foil, dried at 85°C, and then cold pressed, trimmed, stripped, and cut, and finally dried under vacuum conditions at 120°C for 12 hours to obtain the negative electrode sheet.

[0144] ② When the negative electrode sheet includes both the first active layer and the second active layer, the first slurry is coated on the current collector copper foil and dried at 85°C to form the first active layer on the current collector. Then the second slurry is coated on the first active layer, dried at 85°C, and then cold pressed, trimmed, stripped, cut, and finally dried at 120°C under vacuum for 12 hours to obtain the negative electrode sheet.

[0145] (3) Preparation of positive electrode sheet

[0146] The positive electrode active material NCM, the binder polyvinylidene fluoride, and the conductive agent acetylene black were mixed in a ratio of 97:2:1, and then the solvent N-methylpyrrolidone (NMP) was added and stirred to form a positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet.

[0147] (4) Preparation of electrolyte

[0148] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed evenly in a volume ratio of 20:20:60 as an organic solvent, and then LiPF6 is dissolved in the above organic solvent, and fluoroethylene carbonate (FEC) is added. The concentration of LiPF6 in the electrolyte is 1 mol / L, and the mass percentage of FEC is 5wt%.

[0149] (5) Isolation film: PP isolation film is used.

[0150] (6) The negative electrode sheet, the separator, and the positive electrode sheet are stacked and wound in order to obtain a wound battery cell. The battery cell design capacity is 4.5Ah. The battery cell is placed in an outer square aluminum shell, dried, and then injected with electrolyte. After packaging, standing, formation, aging, secondary packaging, capacity, and other processes, a secondary battery is obtained.

[0151] The compositions of the negative electrode sheets in the examples and comparative examples are shown in Table 1.

[0152] Test Case

[0153] (1) Test the energy density of the battery: At 25°C, the prepared battery was fully discharged at 1C, then fully charged at 1C, and fully discharged at 1C, and the actual discharge energy at this time was recorded. At 25°C, the effective length / width / thickness of the battery cell in the 1C fully charged state was tested, and the effective volume V was calculated; the ratio of the battery 1C actual discharge energy D to the effective volume V of the battery cell is the actual energy density E of the battery, E = D / V, where D is in Wh and V is in L.

[0154] (2) Electrode structure stability test: The obtained battery is fully charged at 1C, and the negative electrode is disassembled to obtain the negative electrode. The large surface is folded horizontally, and the folding line is rolled once with a 1kg standard roller. The folding and rolling operations are repeated three times to confirm the light transmission or fracture at the fold of the electrode. It is divided into four levels according to the severity: 1. Fracture: the electrode is disconnected; 2. Severe light transmission: >5 light transmission points; 3. Slight light transmission: 1-5 light transmission points; 4. No light transmission.

[0155] (3) Battery cycle performance test: The prepared battery was subjected to a 0.5C / 1C cycle test at 25°C, and the number of cycles at which the battery decayed to 80% was obtained, which corresponds to the battery cycle performance.

[0156] (4) Battery charging capacity test: Fully charge the battery cell at a rate of 1.2C, disassemble the fully charged battery cell, confirm the lithium deposition at the anode interface, and define 4 levels of lithium deposition based on the percentage of lithium deposition area. 1. No lithium deposition; 2. Lithium deposition area <10%, mild lithium deposition; 3. Lithium deposition area 10% to 30%, moderate lithium deposition; 4. Lithium deposition area >30%, severe lithium deposition.

[0157] Table 1

[0158]

[0159]

[0160] It is understood that in Table 1, the unit of Dv50 is μm. The unit of specific surface area is m 2 / g. The unit of carbon coating thickness is nm. The unit of energy density is Wh / L. The unit of battery cycle performance is circle. In the particle composition of the first graphite, "primary 90% + secondary 10%" means that in the first graphite, the number of primary particles accounts for 90%, and the number of secondary particles accounts for 10%. In the particle composition of the second graphite, "primary 50% + secondary 50%" means that in the first graphite, the number of primary particles accounts for 50%, and the number of secondary particles accounts for 50%.

[0161] It can be seen from Table 1 that, compared with Comparative Example 1, the negative electrode sheets in Examples 1 to 3 have better structural stability, indicating that when the first graphite has a suitable flatness, the structural stability of the negative electrode sheet can be improved.

[0162] Compared with Example 5, the negative electrode sheets in Examples 1 to 3 have better structural stability, indicating that when the primary particles in the first graphite have an appropriate proportion, the structural stability of the negative electrode sheet can be improved.

[0163] Compared with Example 2, the battery corresponding to Example 6 has better charging capacity, indicating that when the second graphite is present, the corresponding battery can obtain better charging performance.

[0164] Compared with Comparative Examples 2 to 4, the battery corresponding to Example 1 can better balance good energy density, negative electrode plate structural stability, cycle performance and charging performance as a whole.

[0165] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0166] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A secondary battery, characterized in that: It includes a negative electrode plate, which includes a negative electrode collector and a negative electrode active layer located on at least one surface of the negative electrode collector, and the negative electrode active layer includes a first active layer; the first active layer contains a first graphite and a first silicon-carbon composite, the flatness of the first graphite is ≥2, and the first silicon-carbon composite includes a porous carbon substrate and a silicon-based material located in the pores of the porous carbon substrate.

2. The secondary battery according to claim 1, characterized in that: The flatness of the first graphite is 2.5-20, and can be optionally 4-16.

3. The secondary battery according to claim 1 or 2, characterized in that: The first graphite includes primary particles; Optionally, the primary particles account for ≥90% of the first graphite.

4. The secondary battery according to any one of claims 1 to 3, characterized in that The first graphite satisfies at least one of the following characteristics: (1) The volume average particle size Dv50 of the first graphite is 12 μm to 18 μm, and optionally 14 μm to 16 μm; (2) The specific surface area of ​​the first graphite is 0.6 m 2 / g~1.4m 2 / g, optionally 0.8m 2 / g~1.2m 2 / g.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The first graphite includes artificial graphite and / or natural graphite; Optionally, the first graphite includes natural graphite, and the mass percentage of the natural graphite in the first graphite is ≤20%.

6. The secondary battery according to any one of claims 1 to 5, characterized in that: The first silicon-carbon composite satisfies at least one of the following characteristics: (1) The volume average particle size Dv50 of the first silicon-carbon composite is 5 μm to 13 μm, and optionally 7 μm to 11 μm; (2) The specific surface area of ​​the first silicon-carbon composite is 1 m 2 / g~8m 2 / g, optionally 1m 2 / g~5m 2 / g; (3) The mass percentage of the first silicon-carbon composite in the first active layer is 5% to 50%.

7. The secondary battery according to any one of claims 1 to 6, characterized in that: The porous carbon substrate satisfies at least one of the following characteristics: (1) The mass percentage of the porous carbon substrate to the first silicon-carbon composite is ≥40%, and optionally 40% to 60%; (2) The porosity of the porous carbon substrate is 30% to 60%.

8. The secondary battery according to any one of claims 1 to 7, characterized in that The silicon-based material satisfies at least one of the following characteristics: (1) The mass percentage of the silicon-based material in the first silicon-carbon composite is ≤ 60%, and optionally 40% to 60%; (2) The silicon-based material includes nano-silicon. Optionally, the grain size of the nano-silicon is ≤6 nm.

9. The secondary battery according to any one of claims 1 to 8, characterized in that The negative electrode active layer further includes a second active layer; the second active layer is located on a surface of the first active layer away from the negative electrode current collector, and the second active layer includes a second graphite.

10. The secondary battery according to claim 9, characterized in that: The surface of the second graphite is coated with a carbon coating layer; Optionally, the carbon coating layer has a thickness of 10 nm to 300 nm, further optionally 20 nm to 100 nm.

11. The secondary battery according to claim 9 or 10, characterized in that: The second graphite includes secondary particles; Optionally, the secondary particles account for ≥50% of the second graphite, and may be 50% to 90%.

12. The secondary battery according to any one of claims 9 to 11, characterized in that: The second graphite satisfies at least one of the following characteristics: (1) the volume average particle size Dv50 of the second graphite is smaller than the volume average particle size Dv50 of the first graphite; Optionally, the volume average particle size Dv50 of the second graphite is 9 μm to 15 μm, and further optionally is 11 μm to 13 μm; (2) The specific surface area of ​​the second graphite is greater than the specific surface area of ​​the first graphite; Optionally, the specific surface area of ​​the second graphite is 0.8 m 2 / g~1.6m 2 / g, further optionally 1m 2 / g~1.4m 2 / g.

13. The secondary battery according to any one of claims 9 to 12, characterized in that: The second active layer further comprises a second silicon-carbon composite; Optionally, the material of the second silicon-carbon composite includes the material of the first silicon-carbon composite; Optionally, the mass percentage of the second silicon-carbon composite in the second active layer is 5% to 50%.

14. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 13.

Citation Information

Cited By

  • Electrode plate containing silicon negative electrode, battery and preparation method of electrode plate

    CN120600764A

  • Secondary battery and electric device

    EP4632834A1

  • Secondary battery, manufacturing method therefor, and electrical device

    WO2026184250A1

  • Lithium-ion secondary battery, battery device and electric device

    WO2026194418A1

  • Battery cell and manufacturing method therefor, battery, and electric device

    WO2026200176A1